Electroacupuncture Mitigates TRPV1 Overexpression in the Central Nervous System Associated with Fibromyalgia in Mice - Doan Thi Ngoc Anh; Yi-Wen Lin (Life)
Background: Fibromyalgia (FM) is characterized by chronic pain, significantly affecting the quality of life and functional capabilities of patients. In addition to pain, patients may experience insomnia, chronic fatigue, depression, anxiety, and headaches, further complicating their overall well-being. The Transient Receptor Potential Vanilloid 1 (TRPV1) receptor responds to various noxious stimuli and plays a key role in regulating pain sensitivity and inflammation. Thus, targeting TRPV1 may provide analgesic and anti-inflammatory benefits. This study investigates the efficacy of electroacupuncture (EA) in alleviating chronic pain in FM through TRPV1 and its downstream molecules in the central nervous system (CNS). Methods: To model FM, we subjected mice to intermittent cold stress (ICS) for three days. The study comprised five rodent groups: Control (CON), ICS, ICS + EA, ICS + Sham EA, and ICS + KO (TRPV1 knockout mice). Results: Our findings revealed that ICS induced allodynia and hyperalgesia in mice by day four, persisting until day 21. EA at 2 Hz and TRPV1 KO significantly decreased both mechanical and thermal hypersensitivity (Withdrawal—Day 14: 2.43 ± 0.19 g; Day 21: 5.88 ± 0.47 g, n = 6, p < 0.05; Latency—Day 14: 2.77 ± 0.22 s; Day 21: 5.85 ± 0.41 s, n = 6, p < 0.05). In contrast, sham EA did not produce significant effects. Additionally, TRPV1 and several pain-related proteins were significantly elevated in the thalamus, somatosensory cortex (SSC), medial prefrontal cortex (mPFC), hippocampus, hypothalamus, cerebellum regions V (CB V), VI (CB VI) and VII (CB VII) after the ICS model. Both EA at the ST36 acupoint and TRPV1 KO mice showed diminished overexpression of pain-related proteins, with the sham EA group showing no significant changes compared to the ICS group. Conclusions: Chronic widespread pain was reduced by EA and TRPV1 KO, with the effects of EA on the TRPV1 pain pathway clearly evident in the CNS after 21 days.